Urinary fibrogenic cytokines ET-1 and TGF-β1 are associated with urinary angiotensinogen levels in obese children - Correia-Costa, Liane; Morato, Manuela; Sousa, Teresa; Cosme, Dina; Guimarães, João Tiago; Guerra, António; Schaefer, Franz; Afonso, Alberto Caldas; Azevedo, Ana; Albino-Teixeira, António (Pediatric nephrology, 2016)
Fibrogenic cytokines are recognized as putative drivers of disease activity and histopathological deterioration in various kidney diseases. We compared urinary transforming growth factor β1 (U-TGF-β1) and endothelin 1 (U-ET-1) levels across body mass index classes and assessed their association with the level of urinary angiotensinogen (U-AGT), a biomarker of intrarenal renin-angiotensin-aldosterone system (RAAS).